2005
DOI: 10.1387/ijdb.052018at
|View full text |Cite
|
Sign up to set email alerts
|

Identical triplets and twins developed from isolated blastomeres of 8- and 16-cell mouse embryos supported with tetraploid blastomeres

Abstract: We studied the developmental potential of single blastomeres from early cleavage mouse embryos. Eight-and sixteen-cell diploid mouse embryos were disaggregated and single blastomeres from eight-cell embryos or pairs of sister blastomeres from sixteen-cell embryos were aggregated with 4, 5 or 6 tetraploid blastomeres from 4-cell embryos. Each diploid donor embryo gave eight sister aggregates, which later were manipulated together as one group (set). The aggregates were cultured in vitro until the blastocyst sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…It is known that tetraploids contribute poorly to derivatives of the fetus and other epiblast derivatives but well to the primitive endoderm and trophectoderm lineages (Tarkowski et al, 1977(Tarkowski et al, , 2001Nagy et al, 1990;James et al, 1995;Goto et al, 2002). However, whether or not tetraploidderived cells express OCT4 was previously unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that tetraploids contribute poorly to derivatives of the fetus and other epiblast derivatives but well to the primitive endoderm and trophectoderm lineages (Tarkowski et al, 1977(Tarkowski et al, , 2001Nagy et al, 1990;James et al, 1995;Goto et al, 2002). However, whether or not tetraploidderived cells express OCT4 was previously unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Some embryonic cells at the ICM site were negative for both CDX2 and OCT4. This finding could explain why tetraploids contribute well to the primitive endoderm and trophectoderm lineages but not to derivatives of the fetus and other epiblast derivatives (Tarkowski et al, 1977(Tarkowski et al, , 2001Nagy et al, 1990;James et al, 1995). Nuclear integrity, nuclear envelope assembly and distribution, recruitment of proteins to the inner nuclear envelope, and chromatin organization are all regulated by the nuclear lamina, which lies at the interface of the nuclear membrane and chromatin and arises from the interaction between membrane-associated proteins and fibrous proteins called nuclear lamins (Stuurman et al, 1998;Goldman et al, 2002;Hutchison, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He suggested that it was not due to a reduced developmental potential of the single blastomere but a matter of the remaining proportion of the embryo volume to form the whole embryo. Assuming that embryos that reach cavitation with a higher number of ICM cells have higher chances to produce ESC lines, Tarkowski et al (2005) [26] suggested a relationship between the number of blastomeres involved in the ESC derivation and the efficiency of the process. In groups starting the derivation with a higher embryo volume, the number of blastomeres at the ICM was higher too thus obtaining a higher efficiency of ESC lines derivation.…”
Section: Discussionmentioning
confidence: 99%
“…While their experiments using siRNA clearly demonstrate that the knock-down of Cdx2 in the lagging two-cell-stage blastomere leads to aberrant blastocyst development and prevents formation of the blastocel cavity, they do not explain how this data can be reconciled with the ability of single 2-, 4-and even 8-and 16-cell-stage blastomeres to form both extraembryonic and embryonic lineages and give rise to full organisms [10]. One possible explanation is that the initial distribution of Cdx2 products promotes Cdx2 expression in certain blastomeres, predisposing them to trophectoderm lineage, but that this effect is cell contact dependent.…”
Section: Significance and Future Perspectivesmentioning
confidence: 96%